Perfil dos usuários e Características do acesso ao núcleo de apoio à saúde da família (NASF) - Souza, Fernando Leonardo Diniz (2014)
With the creation of Family Health Support Centres (NASF) in 2008, as part of a health promotion initiative within primary health care, it has become important to identify the individuals who participate in the service and to determine how they have come to use the program. This is important considering that the NASF is not expected to be a gateway to the system, with multi-professional support for family health care teams. Given the short time that the NASF has existed to date, a large number of studies and analyses, which might better identify its place within the primary care dynamic, have not been possible. This study therefore has the following objectives: to describe NASF user profiles and to identify how users accessed the program from within a medium-sized municipality of Minas Gerais. For this purpose, transversal research was conducted with questionnaires administered to a sample of 300 users of three NASF teams active in the chosen municipality, to identify their sociodemographic, health and NASF access characteristics. Univariate and bivariate analyses were conducted on user characteristics; access characteristics were examined via bivariate analysis, with referral to the NASF by an SUS (Unified Health System) agent considered an dependent variable. The results show that the NASF receives a greater percentage of females, self-identified as white, of low-income, loweducation, with predominance in an older age group, sometimes without healthrelated complaints and who seek NASF services after hearing about it by word-ofmouth. Men, who are represented by a smaller number, are on average older and present with more health complaints. For both sexes, referrals occur more frequently when there are health problems or complaints, and account for 29% of users; the remaining 71% reach NASF by walk-ins, through information or suggestion by friends or acquaintances. These results show that in the municipality studied, the NASF has not functioned in accordance with its regulations. However, by allowing access to all those who want or need multi-professional care, with the idea of health promotion or recovery, the NASF has fulfilled the universal and integral guidelines of the SUS. Nevertheless, the low number of males and people who self-identify as white suggests that effort is necessary to improve the delivery of equality proposed by the SUS. These results suggest a need for the cautious monitoring of the use of this resource, to guarantee that access is not obstructed for those who lack a specific health complaint and who want to benefit from this service, but ensuring also that there are no obstacles for those who need the service to preserve their health. In other words, we must ensure that walk-ins do not prevent or hinder patient access by referral, without, however, closing the doors of this service. Key words: Family health support centres; primary health care; health promotion.